51.3k views
2 votes
What transformation is made from f(x) → f(-x)?

A) reflection across the y-axis

B) rotation around the origin

C) reflection across the x-axis

D) sliding it down

2 Answers

4 votes

Answer:

the answer is reflection across the y-axis

Explanation:

That's the correct answer (-.-)

User Jvoll
by
6.1k points
7 votes

Answer:

A) reflection across the y-axis

Explanation:

If
f(x)=f(-x), then this says that two
y-coordinates are equal for opposite values of
x.

Let
(a,b) a point on
f.

Then
f(a)=b.

We also know that
f(-a)=b and therefore
(-a,b) is also a point on the graph.

If you graph [/tex](-a,b)[/tex] and
(a,b) you will see they are symmetrical to each about the
y-axis.

Example if given both
f(x)=f(-x) and
f(2)=3, then
f(-2)=3. This means both (2,3) and (-2,3) are points on the graph.

Here is what those two points look like on a Cartesian Plane (please see graph in picture).

What transformation is made from f(x) → f(-x)? A) reflection across the y-axis B) rotation-example-1
User Atzuki
by
6.0k points